COLOUR HOMOGENISATION OF BEECH WOOD BY STEAM TREATMENT - Tolvaj László (DREWNO - PRACE, NAUKOWE, DONESIENIA, KOMUNIKATY, 2009)
In our study beech (Fagus silvatica L.) samples containing white and red heartwood were steamed to obtain colour homogenisation. Wide range of steaming temperatures (80-120 degrees C) was applied for wet (47%), semi-wet (28%) and dry (8%) samples. All temperature values were effective in minimising the colour difference between white and red heartwood of beech. Below 100 degrees C the colour change was similar irrespective of the temperature value. Determinative part of the colour change occurred during the first 12 hours of the process. It was found that the optimum homogenisation time is 0.5-2 days depending on the applied temperature value. The initial moisture content had no effect on the colour change if it was above the fibre saturation point. The colour shift was less intensive in the case of initially dry samples than in the case of wet samples. Colour homogenisation of beech wood by steaming below 100 degrees C is not recommended if the timber is initially dry.